Validation of the HPLC-PDA method for detection of eluxadoline and rifaximin in rat plasma and application in a pharmacokinetic study - Vijendar Reddy Karla; Babji Palakeeti; M. Raghasudha; Raghu Chitta (SpringerOpen, 2022)
Abstract Background A precise, simple, accurate, and quick HPLC-PDA method for the determination of eluxadoline and rifaximin in rat plasma was developed and validated in this study. In this method, Loperamide hydrochloride was used as the internal standard and plasma samples were prepared using a liquid-liquid extraction technique for which acetonitrile was a solvent. An Agilent Symmetry C8 column (5 µm, 250 mm × 4.6 mm) at 283 nm and isocratic elution using HPLC grade acetonitrile and 7 mM TEA (pH 2.5) with a ratio of (40: 60 v/v) was used as a mobile phase and the flow rate employed was 1 mL min−1. A satisfactory chromatographic separation was accomplished. Results An HPLC-PDA method for the determination of eluxadoline and rifaximin with retention times of 3.06 and 7.82 min, respectively, was developed. The calibration curves appear linear for both eluxadoline and rifaximin in the range of 5-200 ng mL−1 and 10-400 ng mL−1, and the corresponding correlation coefficient values were found to be 0.9999 and 0.9998 respectively. Lower limits of quantification (LLOQ) for eluxadoline and rifaximin were evaluated to be 5.0 ng mL−1 and 10.0 ng mL−1, respectively. The accuracy and precision results in all validation experiments were within the acceptance limits of FDA guidelines. Conclusion The developed HPLC-PDA approach was fully validated to meet the USFDA guidelines for bioanalytical method validation in terms of precision, accuracy, and stability. The presented approach could be beneficial for the determination of ELX and RFX in rat plasma, according to validation parameters. This is one of the efficient method to study the pharmacokinetics of ELX and RFX in rats. Graphical abstract